2018
DOI: 10.1111/pan.13469
|View full text |Cite
|
Sign up to set email alerts
|

Caudal and intravenous dexmedetomidine similarly prolong the duration of caudal analgesia in children: A randomized controlled trial

Abstract: Summary Background Dexmedetomidine can prolong the duration of action of a local anesthetic agent, but the route of administration that is the most beneficial remains unclear. The purpose of this study was to compare the clinical effectiveness of caudal or intravenous dexmedetomidine administration on postoperative analgesia in children undergoing inguinal hernia repair given caudal levobupivacaine. Methods This was a prospective, randomized, double‐blinded, placebo‐controlled trial. Ninety ASA I subjects, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…315 potentially relevant articles are identi ed initially. Finally, six RCTs are included in the meta-analysis [11,13,[17][18][19]25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…315 potentially relevant articles are identi ed initially. Finally, six RCTs are included in the meta-analysis [11,13,[17][18][19]25].…”
Section: Resultsmentioning
confidence: 99%
“…The dose of dexmedetomidine ranged from 0.3 µg/kg to 1.0 µg/kg. Among the six included RCTs, two trials reported analgesic consumption [19,25], two trials reported number of rescue analgesics and time to rst analgesia [18,19], two trials reported emergence agitation [18,25], as well as two trials reported pain scores at 1 h and 2 h [17,19]. Jadad scores of the six included studies vary from 3 to 5, and all six studies have high-quality based on the quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRISMA flowchart shows the process of literature screening, study selection, and reasons for exclusion ( Figure 1). Among the trials identified from the literature search strategy, five RCTs [22][23][24][25][26] including 244 children met the inclusion criteria. [23][24][25][26] hydrocele, 24 circumcision, 24 and hypospadias 22,24,25 operation.…”
Section: Re Sultsmentioning
confidence: 99%
“…Among the trials identified from the literature search strategy, five RCTs [22][23][24][25][26] including 244 children met the inclusion criteria. [23][24][25][26] hydrocele, 24 circumcision, 24 and hypospadias 22,24,25 operation. All trials combined A2AAs with long-acting local anesthetics (0.25% bupivacaine 22,24 or levobupivacaine 23,25,26 ) in dosages of 1 mL/kg, [24][25][26] 0.75 mL/kg, 23 or 0.5 mL/ kg.…”
Section: Re Sultsmentioning
confidence: 99%